Skill Savings Accounts: Reimagining Employee Education Benefits (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
As technology, automation, and global competition make a wide range of skills obsolete at an astounding pace, the United States faces significant upskilling and reskilling challenges. In response to these challenges to the nation’s economy and productivity posed by what amounts to a growing skills gap,  the U.S. Chamber of Commerce Foundation has reimagined existing employee education benefits to create a more worker-centered solution: the Skill Savings Account. This innovative financial tool, which was introduced and discussed in this session, offers a new way to fund learning and skill-building needs, while also incentivizing employees to keep their skills current. In effect, Skill Savings Accounts can provide easy access to money that any employee can use to purchase a wide range of upskilling and reskilling opportunities (such as trainings, long- and short-term courses, community-based nonprofit skill offerings, bootcamps, and online courses) that, importantly, can be documented and verified digitally.  As this session emphasized, such a reimagining of workforce investment and employee education benefits can help to build a powerful skills development marketplace and, in so doing, contribute to economic growth and competitiveness.Keywords: skills gap, skill-building needs, skill savings account